FEATURES OF THE FORMATION OF THE LAND MARKET IN UKRAINE: LEGAL ASPECT - Zhmur, Nataliia; Pavlovich, Larisa (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of the article is to consider the formation of the land market in Ukraine, to determine its features, positive and negative sides, as well as the impact on the development of the economic aspect of the state. Research methods: methods of analysis and synthesis were used - during the study of the legislative framework of Ukraine in the context of the formation of the land market; the method of comparison - determination of the price factor of different regions, as well as the identification of positive and negative sides in the formation of the market, historical, cognitive-analytical and statistical methods. Results: the peculiarities of the formation of the land market were characterized. The periodization of its formation, the positive and negative aspects of its implementation and the attitude of different categories of people to the land market are determined. The statistics of market operations, the variety of prices in different regions of Ukraine were considered. The legislative framework and legal aspects of regulation have been developed. The question of the functioning of the land market in the conditions of martial law has been studied. Discussion: the chronology of the land market and the peculiarities of its functioning, as well as the problems of functioning during martial law, were analyzed. Based on the analyzed and researched land market, a general and broad concept of the land market was formed. The legal provision of the land market is analyzed.